2008
DOI: 10.1021/es071687r
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Dioxin Precursors in Pesticide Formulations and Environmental Samples As a Source of Octachlorodibenzo-p-dioxin in Soil and Sediment

Abstract: An as yet unidentified origin of elevated concentrations of polychlorinated dibenzo-p-dioxins (PCDDs) in soil and sediment has repeatedly been described from different locations around the world, including Australia. Natural sources have been hypothesized to account for such contamination, which is characterized by a distinctive dioxin profile, in particular, elevated levels of octachlorodibenzo-p-dioxins (OCDD) as well as relatively low contributions of polychlorinated dibenzofurans (PCDFs). The present study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 37 publications
(102 reference statements)
2
26
1
Order By: Relevance
“…Note, however, that there are some slight variations between relative effect potencies in AhR‐CAFLUX and international toxic equivalency factors that were applied in a previous study. Holt et al found that such high concentrations of dioxin‐like chemicals in soil and sediment were a result of the extensive use of pesticides in agriculture and that pesticides and their impurities play an important role in the dioxin contamination of Australian soil and sediment.…”
Section: Resultsmentioning
confidence: 99%
“…Note, however, that there are some slight variations between relative effect potencies in AhR‐CAFLUX and international toxic equivalency factors that were applied in a previous study. Holt et al found that such high concentrations of dioxin‐like chemicals in soil and sediment were a result of the extensive use of pesticides in agriculture and that pesticides and their impurities play an important role in the dioxin contamination of Australian soil and sediment.…”
Section: Resultsmentioning
confidence: 99%
“…Dioxins can be formed via degradation of carbon species in the presence of a chlorine source at temperature range 200-600 °C. On the other hand, they can be formed via precursor compounds, such as pentachlorophenol chlorinated diphenylethers and polychlorinated biphenyls or chlorobenzenes which are used as fungicidal and bacterial agent in wood treatment (Weber 2007;Holt et al 2008).…”
Section: Dioxins and Related Pollutantsmentioning
confidence: 99%
“…[30][31][32] Im et al [32] also found OCDD in soil samples from a remote mountainous area and suggested that it was dominantly deposited from the air as that study area was not directly influenced by human activities. Besides, it was reported that pesticides of pentachlorophenol (PCP) and related chlorinated phenoxyphenols (PCPPs) that have previously applied to soil may serve as potential precursors [33] for the OCDD formation in the presence of UV or natural sunlight. [34] This may explain the higher levels of OCDD detected on top soils as compared with those of lower soil layers in our UV-exposure experiments.…”
Section: Levels Of Detected Dioxin Congenersmentioning
confidence: 99%